Adsorption of chloroquine, propranolol, and metformin in aqueous solutions using magnetic graphene oxide nanocomposite (2023)
The work proposes the application of a nanocomposite formed by graphene oxide and magnetite to remove chloroquine, propranolol, and metformin from water. Tests related to adsorption kinetics, equilibrium isotherms and adsorbent reuse were studied, and optimization parameters related to the initial pH of the solution and the adsorbent dosage were defined. For all pharmaceuticals, adsorption tests indicated that removal efficiency was independent of initial pH at adsorbent dosages of 0.4 g L-1 for chloroquine, 1.2 g L-1 for propranolol, and 1.6 g L-1 for metformin. Adsorption equilibrium was reached within the first few minutes, and the pseudo-second-order model represented the experimental data well. While the equilibrium data fit the Sips isotherm model at 298 K, the predicted maximum adsorption capacities for chloroquine, propranolol, and metformin were 44.01, 16.82, and 12.23 mg g-1, respectively. The magnetic nanocomposite can be reused for three consecutive cycles of adsorption-desorption for all pharmaceuticals, being a promising alternative for the removal of different classes of pharmaceuticals in water.